Retrospective analysis of stereotactic body radiation therapy efficacy over radiofrequency ablation for hepatocellular carcinoma. (February 2019) - Kim, Nalee; Kim, Hyun Ju; Won, Jong Yun; Kim, Do Young; Han, Kwang-Hyub; Jung, Inkyung; Seong, Jinsil
Highlights: SBRT provides comparable local control to RFA even with more advanced, recurrent, and larger tumors. Significant difference in local control favoring SBRT was observed in the propensity score matching, and inverse probability of treatment weighting. SBRT could be an effective alternative treatment for tumors larger than 2.0 cm or for those located in subphrenic region. Abstract: Background and purpose: To evaluate the efficacy of stereotactic body radiotherapy (SBRT) and radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC). Methods and materials: Patients treated for HCC between 2012 and 2016 were reviewed. Among these, 668 patients who underwent RFA of 736 tumors and 105 patients who underwent SBRT of 114 tumors were included. Using propensity score matching (PSM) to adjust for clinical factors, 95 tumors were selected from each treatment arm. Freedom from local progression (the primary endpoint, FFLP) was compared before and after adjustment with PSM. Results: At baseline, SBRT-treated tumors were more advanced, larger (median, 2.4 vs. 1.6 cm), and more frequently located in the subphrenic region than RFA-treated tumors ( P  < .001). The median follow-up was 21.5 (interquartile range, 11.2–36.7) months. Before PSM, the 2-year FFLP rates were 76.3% for the SBRT group and 70.2% for the RFA groups, respectively. After PSM, the 2-year FFLP rates were 74.9% for the SBRT group and 64.9% for the RFA group, respectively. The local control rates were not significantly different. The Cox proportional hazards model revealed the treatment modality as an independent predictor of local recurrence favoring SBRT in the entire cohort and in the PSM model. Elevated tumor markers, tumor location (subphrenic region), and tumor size (>2.0 cm) were also independent predictors of local progression. Conclusion: SBRT appears to be an effective alternative treatment for HCC when RFA is not feasible due to tumor location or size.